From hogudanja to the screen: A review of the Korean slavery using data mining. - Fuentes-Quirós, Laura (My University, 2024)
Until the 19th century, Korea was a state with a very hierarchical society in which people from the lowest social class were considered possessions and labor that served the yangban families, temples, and government offices. Slavery was fundamental to the economy during the Joseon dynasty, since slaves or nobi functioned as the main productive workers and brought prestige to the elites. One kind of document that shows the existence of slaves is the household register or hogudanja, a census record developed to administer the tax system and that helped to organize military service at the national level. The documents included the members of each family and the nobi they had, so they could facilitate the demographic study of the Korean Peninsula. This research focuses on the development of a computer application for the automation of the study of Korean slaves declared in the hogudanja. Computational techniques cover much of the process, including acquiring primary sources, processing the data, and finally representing them using a graph database. The result allows us to visualize the distribution of declared slaves in large-scale digitized documents to study their evolution, family relationships between nobi, and to compare official family records and drafts submitted by families to examine whether there are discrepancies. This study shows the possibilities of Digital Humanities applied to the study of the Korean history. Future research will allow the application to be adapted and extrapolated to other types of structured historical documents.
Keywords: Humanidades digitales; Esclavitud - Corea; Minería de datos; Digital Humanities; Joseon; Korea; Census; Slavery